COMPUTER FILTERING IONOGRAMS OF IONOSPHERIC HF COMMUNICATION RADIO CHANNELS AND ALGORITHM OF DETERMINING SIGNAL-TO-NOISE RATIO - Ivanov, Vladimir; Ivanov, Dmitriy; Ryabova, Natalya; Ryabova, Mariia; Chernov, Andrei; Elsukov, Alexey (Journal of Applied Engineering Science, 2018)
Algorithm and software were developed to obtain ionograms of oblique sounding of wideband radio channel. We present the algorithm of computer filtration of ionograms with the use of median equalizing method. Algorithm and software were developed to estimate signal-to-noise ratio in ionospheric HF channels.